Osteocalcin and vascular function: is there a cross-talk? - Alexander Tacey; Alan Hayes; Anthony Zulli; Itamar Levinger (Elsevier, 2021)
Background: The bone-derived protein osteocalcin (OC), in its undercarboxylated (ucOC) form, has a beneficial effect on energy metabolism and may be a future therapeutic target for metabolic diseases. Increasing evidence suggests a link between ucOC and cardiovascular disease (CVD) development; however, the exact relationship is conflicting and unclear. Scope of review: The aim of this review was to summarise the current research examining the interaction between OC and vascular dysfunction, the initiating stage in the development of atherosclerosis and CVD. Major conclusions: In humans, the association between OC and vascular function is inconsistent. Several studies report that total OC (tOC) is associated with adverse function or beneficial function, whereas others report that tOC and ucOC has no effect on vascular function. The conflicting data are likely due to several methodological inconsistencies, in particular the lack of studies reporting circulating ucOC levels. In animal models, the direct administration of ucOC to isolated blood vessels ex vivo produced minimal changes in endothelial function, but importantly, no adverse responses. Finally, in human endothelial and vascular smooth muscle cells, ucOC treatment did not influence classical markers of cellular function, including endothelin-1, vascular adhesion molecule-1 and monocyte chemoattractant protein-1 after exposure to high glucose and inflammatory conditions. The lack of adverse effects in ex vivo and in vitro studies suggests that ucOC may be targeted as a future therapeutic for metabolic diseases, without the risk of detrimental effects in the vasculature. However, further studies are needed to confirm these findings and to investigate whether there is a direct beneficial influence of ucOC.